Synthesis of Novel AZO-Aniline with different substituted Anilines and study of their Biological Activity - Nehete, C. A. (International Journal of Pharmaceutical & Biological Archive, 2017)
The compounds containing –N=N-C6H3-(R)NH2 (azo-aniline) were prepared from 5-Amino-salicylicacid with differently substituted aniline respectively by stirring at low temperature. The synthesized products were tested in process and on completion of reaction by TLC technique. The final products were characterized by physical viz. m.p., analytical viz. TLC, instrumental viz. UV-Vis and FTIR spectral technique. Their biological activities were also evaluated.